Transarterial Embolization in Neonatal Kasabach–Merritt Syndrome - Wang, Yinghao; Wang, Song; Wang, Lili; Bi, Shaohua; Zhang, Jian; Zha, Ping; Dai, Liying (Frontiers in Pediatrics, 2021)
Background: Kasabach-Merritt syndrome (KMS) is characterized by rapidly enlarging hemangiomas and persistent thrombocytopenia, which may result in visceral hemorrhage and disseminated intravascular coagulation (DIC). This study aimed to evaluate the value of transarterial embolization (TAE) in neonatal KMS patients. Patients and Methods: Clinical course of eleven neonates with KMS underwent TAE in the Department of Neonatology, Anhui Children's Hospital, Anhui Medical University, China were reviewed retrospectively. Results: Eleven neonates (9 males, 2 female) admitted to our hospital between the age of 1 hour and 6 days with KMS. All were born with progressively enlarged hemangiomas and persistent thrombocytopenia. The largest lesion had its maximum size reached 15 cm x 8 cm x 8 cm. Eight patients had cutaneous hemangiomas (1 right face; 1 oropharynx; 1 left upper arm; 2 back; 1 left lumbar; 1 right lower leg; 1 right thigh); and 3 patients had liver hemangiomas. All 11 patients underwent TAE. Nine patients underwent two TAEs and 2 patients underwent only one embolization procedure. They all obtained >80% devascularization of their lesions without major complication. The platelet count increased 2~5 days after treatment, and reached normal count and coagulation profile 18~28 days after the TAE. Conclusions: TAE is a safe and effective alternative therapy for neonatal KMS patients。